Distributed event-triggered synchronization for robotic teleoperation systems with randomly occurring gain fluctuations. (23rd April 2018) - Ma, Chao; Kang, Erlong
This article investigates the synchronization problem of robotic teleoperation systems by developing a novel event-triggered networking strategy. Furthermore, the randomly occurring controller gain fluctuations are considered for the robotic teleoperation systems, such that more robustness can be obtained in the controller implementation. Based on model transformation, sufficient synchronization conditions are derived by employing the Lyapunov–Krasovskii method. Then, distributed controllers are designed for achieving the mean square synchronization. Finally, the effectiveness and feasibility of our proposed control strategy are demonstrated by an illustrative example.